Nausea, Vertical Gaze Palsy, and Excessive Sleep: An Unusual Presentation of Pediatric AQP4-Antibody Positive Neuromyelitis Optica Spectrum Disorder - Oberholzer, Tatjana A.; Plastina, Leonie; Wille, David; Sirin, Selma; Hackenberg, Annette (Neuropediatrics, 2025)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare neuroinflammatory disease with an annual incidence of less than 1 case in 1,000,000 in the White population and a median age of onset at 40 years. NMOSD usually presents with optic neuritis and longitudinally extensive transverse myelitis. Various brainstem, cerebellar, diencephalic, and hemispheric symptoms may also occur. Early diagnosis and treatment are crucial for symptom management and prevention of relapses and disability. We report the case of a prepubertal girl, highlighting unique clinical and magnetic resonance imaging features and the risk of early parenchymal damage.
Keywords: vertical gaze palsy; narcolepsy; NMOSD; pediatric onset; AQP4-antibody